Les pratiques enseignantes dans le contexte des Olympiades de la formation professionnelle au Québec : entre ombre et lumière d’un « travail partagé » - Balleux, André (Canadian Journal of Education/Revue canadienne de l’éducation, 2011)
<!–StartFragment–> In an effort to reassert the value of vocational education, the Quebec ministry of Education launched the Skills Competition project in 1992. Patterned on the Olympic Games, these trades and technology competitions allow the graduates of vocational education to compare themselves with the best in their field in public events which are broadly mediatised. But behind the festive and showy nature of the competitions lies an extraordinary commitment on the part of teachers and students. The research presented here lead us to discover a context of innovative teaching practices; collaborative practices of "shared work”, of teaching practices within and outside the classroom, and within and beyond the scope of work. For students, results showed a new relationship to learning and skills improvement. <!–EndFragment–>